Transcriptome Analysis Reveals Key Genes in Response to High-Temperature Stress in Rhododendron molle - Linshi Wu; Yan Liu; Xinyun Liu; Qiaoyun Li; Xinyu Yi; Chan Chen; Ling Wang; Juyang Liao (BioResources)
Rhododendron molle is a deciduous rhododendron, a high-altitude plant prized for its medicinal and ornamental properties. A major challenge when introducing this plant to lower altitudes is understanding its response to high-temperature stress. Using transcriptome analysis, this study examined leaves under varying temperatures, identifying 344,593 transcripts, 124,901 Unigenes, and 12,089 differentially expressed genes (DEGs) at 36 °C high-temperature stress (ST). At 42 °C high-temperature stress (SY), 12,032 DEGs were found, indicating a significant impact of temperature on gene expression. A Gene Ontology analysis (GO) revealed that these DEGs are mostly involved in stress response, catalytic activity, binding, transporter activity, and immune processes. A Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis highlighted enrichment in pathways such as plant-pathogen interaction and spliceosomes, suggesting their key roles in the temperature stress response. Key genes such as Brassinosteroid-Insensitive 1-Associated Receptor Kinase (BAK1) and Pathogenesis-Related Gene Transcription Activation Factor (PTI6) were upregulated under ST stress, whereas heat shock proteins (HSP83A) and HSP90-1 were downregulated under SY. These findings offer insights into the molecular response of Rhododendron molle to high temperature, aiding further research in this area and potentially improving the plant’s cultivation and application.